2016
DOI: 10.1016/j.ijsu.2016.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous acupoint electrical stimulation pain management after surgical abortion: A cohort study

Abstract: Transcutaneous acupoint electrical stimulation shows potential as an adjunct to conventional pain treatment following surgical abortion in nulliparae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Considered together, the results of the present study are supported by a number of studies that showed that TEAS can be successfully used to manage pain. [24][25][26] In addition, it refined the results of one of our previous studies 13 in determining which patients could benefit the most from TEAS and under which conditions. Nevertheless, this study has some limitations.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Considered together, the results of the present study are supported by a number of studies that showed that TEAS can be successfully used to manage pain. [24][25][26] In addition, it refined the results of one of our previous studies 13 in determining which patients could benefit the most from TEAS and under which conditions. Nevertheless, this study has some limitations.…”
Section: Discussionmentioning
confidence: 91%
“…At present, TEAS intervention during surgical abortion pain management included only studies in nulliparous women. 13 Considered together, the results showed that the best analgesic effect of TEAS during surgical abortion was achieved in women aged between 25 and 30 years; nulliparous women but at least at their second pregnancy (G ≥2 P 0 A ≥1 ); using the Sanyinjiao (SP 6) and Taichong (LR 3) acupoints; and using a stimulation time of 15 min. In order to reflect the stability and fluctuation of the vital signs, BP, MAP, SPO 2 and HR were monitored, and there were no significant fluctuations during surgical abortion under TEAS.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations